Urban Land Policy For Indonesia: The Need For Reform - Setiawan, Bakti (Journal of Regional and City Planning, 2001)
Urban land policy and management in Indonesia are very weak; some problems can be identified i.e. problems in land tenure system, land registration systems, land delivery and acquisition, land use planning, land taxes, and land ceiling. At the same lime, the process of urbanization and urban growth are increasing and the problem of urban land is getting more complex and capable of creating conflicts. Considering the importance of the efficient use of land and its equal distribution for a sustainable development, this paper argues that reformation in land policy and management in Indonesia is needed both at the level of policy guidelines and at the level of implementation.